Frequency-Specific Regional Homogeneity Alterations in Tourette Syndrome - Lou, Yu-Ting; Li, Xiao-Long; Wang, Ye; Ji, Gong-Jun; Zang, Yu-Feng; Wang, Jue; Feng, Jian-Hua (Frontiers in Psychiatry, 2020)
Tourette syndrome (TS) is a developmental neuropsychiatric disorder with with onset during childhood-onset. Given the Because of its complex spectrum of phenotypes, the underlying pathophysiology of TS are is still unclear. Resting-state functional magnetic resonance imaging (RS-fMRI) has discovered demonstrated aberrant spontaneous neural synchronization in conventional frequency band (0.01-0.08 Hz) in TS. No study reports about these published studies have reported abnormalities of local synchronization across different frequency bands. We estimated the alterations of local synchronization across five bands ranging from 0 to 0.25 Hz. Seventy-nine children with TS and 63 age-, sex- and handedness handedness-matched healthy children were recruited. Resting-state functional magnetic resonance imaging and frequency-Frequency-specific regional homogeneity (ReHo) and independent component analysis were used to identify functional alterations between TS and healthy children. TS patients showed significantly increased ReHo in the left precentral gyrus and decreased ReHo in the right right operculum. Abnormal ReHo alterations of the superior frontal gyrus, superior parietal gyrus, anterior cingulate gyrus, putamen, superior temporal gyrus gyrus, and operculum was were observed in different frequency bands. TS patients showed increased connectivity of the right superior frontal gyrus within the left executive control network. In addition, a significantly negative correlation was found between the YGTSS Yale Global Tic Severity Scale (YGTSS) vocal score and the ReHo values of the right right operculum in the lowest and highest frequency bands (0-0.01Hz 01 Hz and 0.198-0.25 Hz), while a significant positive correlation was found between YGTSS motor score and altered connectivity of the right superior frontal gyrus. The present study revealed frequency-specific abnormal alterations of ReHo in the whole brain and altered connectivity within the executive control network of TS children. Its neural importance and clinical practicability need to be require further investigatedinvestigation.